2 - Gestion des espaces publics au Congo-Brazzaville : le cas des parkings - Ngodi, Etanislas (Africa Development, 2021)
The issue of public spaces in Congo-Brazzaville is at the heart of municipal political debates. At the level of public transport, the management of public spaces remains above all in the hands of the mayor’s office and municipal councillors. The agreements between these authorities and the contractors running public transport only partially meet public service objectives. Certain public spaces appear as niches for public transport: parking lots. Two types of parking can be identified: the private parking lots of public and private administrations and public parking lots. The second case is the focus of this study. To date, the legal and regulatory void regarding the management of public spaces and the priority plan on public transport does not include the regulation of public parking lots in the major cities of Congo. Public spaces have become a locus for the development of economic activities. Public transport parking areas are privatized by social actors and increasingly appear as new forms of survival strategies. The occupation of the street (bus and taxi terminals and parking places) under various mobile and sedentary, temporary and permanent forms, makes parking lots a focus of study as a territory for informal activities and the continuity of traffic functions, as well as the failure to manage public spaces properly. Public transport management planning is not a matter of payment of road and parking taxes alone.